Integrasi Prinsip Maqasid al-Syariah dalam Hukum Kepailitan di Indonesia - Dewi Bulan Permatasari Ainurrochmah; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to examine the integration of the principles of maqāṣid al-syarī‘ah into Indonesia’s bankruptcy law as a step towards a more just, ethical, and welfare-oriented debt settlement system. Using a normative legal approach and conceptual analysis method, this research explores legal sources in Indonesia, particularly Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), and analyzes relevant literature on maqāṣid al-syarī‘ah. The findings indicate that the principles of maqāṣid al-syarī‘ah, especially ḥifẓ al-māl (protection of wealth), ḥifẓ al-nafs (protection of life), and ḥifẓ al-dīn (protection of religion), have significant potential to be incorporated into Indonesia's bankruptcy framework. The study suggests that aligning bankruptcy law with Islamic ethical foundations can offer a more holistic resolution model that upholds justice and public benefit in financial distress situations.